Effect of ISPAD Anaerobic Digestion on Ammonia Volatilization from Soil Applied Swine Manure - Susan King; Michael Schwalb; David Giard; Joann Whalen; Suzelle Barrington (Applied and Environmental Soil Science)
Swine manure subjected to in-storage psychrophilic anaerobic digestion (ISPAD) undergoes proteins degradation but limited NH3 volatilization, producing an effluent rich in plant-available nitrogen. Accordingly, ISPAD effluent can offer a higher fertilizer value during land application, as compared to manure of similar age stored in an open tank. However, this additional nitrogen can also be lost by volatilization during land application. The objective of this study was therefore to measure NH3 volatilization from both ISPAD and open tank swine manures when applied to 5 different soils, namely, washed sand, a Ste Rosalie clay, an Upland sandy loam, a St Bernard loam, and an Ormstown loam. This research was conducted using laboratory wind tunnels simulating land application. The five experimental soils offered similar pH values but different water holding capacity, cation exchange capacity, cation saturation, and organic matter. After 47 h of wind tunnel monitoring, the % of total available nitrogen (TAN or NH4 + and NH3) volatilized varied with both manure and soil type. For all soil types, the ISPAD manure consistently lost less NH3 as compared to the open tank manure, averaging 53% less. Lower volatile solids content improving manure infiltration into the soil and a more complex ionic solution explain the effect of the ISPAD manure advantages. This was reinforced by the St Bernard sandy loam losing the same nitrogen mass for both manures, because of its higher pH and buffer pH coupled with an intermediate CEC resulting in more soil solution NH3. Within each manure type, % TAN volatilized was highest for washed sand and lowest for the clay soil. As a result, ISPAD manure can offer up to 21% more plant-available nitrogen fertilizer especially when the manure is not incorporated into the soil following its application.